A highly corrosion-resistant and controllably degradable medical magnesium alloy and a preparation method thereof
By adding calcium, yttrium and lanthanum elements to the magnesium-zinc-based alloy and using deformation processing and heating treatment methods, the problem of local corrosion and insufficient mechanical properties of magnesium alloy in the human body is solved, and the effect of high corrosion resistance and uniform and controllable degradation is achieved.
Patent Information
- Application Number
- CN202411803396.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing medical magnesium alloys are prone to local corrosion in the human body, resulting in premature failure of the implant and may cause emphysema and alkaline poisoning. At the same time, the mechanical properties of magnesium alloys cannot meet the needs of high-mechanical performance implants.
By adding a small amount of low-potential calcium, yttrium and lanthanum elements to the magnesium-zinc-based alloy, and using deformation processing and heating treatment control methods, the uniform and fine dispersion distribution of the second phase in the magnesium matrix is promoted, thereby improving the mechanical properties and corrosion resistance of the alloy.
The high corrosion resistance and uniform and controllable degradation of magnesium alloy are achieved, which avoids the occurrence of local corrosion, significantly improves the mechanical properties of magnesium alloy, and meets the needs of high mechanical properties implants.
Smart Images

Figure CN119265439B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of degradable medical metal materials, and specifically relates to a highly corrosion-resistant controllably degradable medical magnesium alloy and a preparation method thereof. Background Art
[0002] As the lightest structural metal material, magnesium alloy is well known for its excellent biocompatibility and high specific strength. The density of magnesium is 1.74 g / cm 3 About the same as human bone density (1.75 g / cm 3 ). Moreover, the elastic modulus of Mg is about 45 GPa, which is closer to the elastic modulus of human bone (20GPa) than other inert metal implant materials, such as titanium and stainless steel, and can effectively avoid stress shielding. In addition, magnesium is an essential nutrient for the human body and exists in bones, teeth and soft tissues. In addition, magnesium is also an essential element for maintaining the structure and function of bone cells and can promote the proliferation and differentiation of bone cells. Studies have shown that lanthanum (La) is beneficial for inhibiting tumor proliferation, and calcium (Ca) is an important component of human bones and an optional element for alloying medical magnesium alloys. At present, medical magnesium alloy materials have been widely used in the field of bone plant materials such as bone nails, bone plates, bone tissue engineering scaffolds, etc. due to their good biocompatibility, strength and toughness, and degradability. They have the effect of promoting osteogenesis, and can be self-degraded and eliminated after bone healing, which can avoid the harm of secondary surgery to the human body. However, due to the high chemical activity of magnesium, the low standard electrode potential (-2.37 V / SHE), and the PBR (Pilling-Bedworth ratio) of the surface MgO oxide film of 0.81 (less than 1), it has the characteristics of looseness and non-denseness. Therefore, magnesium and its alloys are very prone to local corrosion in the human body. The occurrence of local corrosion will lead to accelerated corrosion of magnesium implants and rapid loss of mechanical properties, resulting in premature failure of the implants before reaching the service life. Therefore, how to promote the uniform corrosion of magnesium and its alloys in the physiological environment and achieve uniform and controllable degradation is the key to solving the premature failure of magnesium implants. In addition, the rapid corrosion of magnesium alloys will lead to the production of a large amount of hydrogen and hydroxide, which can easily lead to emphysema and alkali poisoning. Studies have shown that ultrapure magnesium has good corrosion resistance in the physiological environment, but the mechanical properties of pure magnesium are extremely poor, with a yield strength of only about 20 MPa, and it cannot be used as a biological implant. This is because some biological implants require alloys to have high mechanical strength, such as bone nails and bone plates. Therefore, designing medical magnesium alloys with good biocompatibility, high corrosion resistance and excellent mechanical properties is the key to solving the application of magnesium alloys in degradable implants.
[0003] A Chinese patent (publication number CN116694943A) discloses a method for preparing a degradable medical magnesium alloy, which effectively improves the yield strength of the magnesium alloy by adding the element Sr to the Mg-Zn-Mn-Zr magnesium alloy. On the other hand, the element Sr is an essential trace element for the human body and has no cytotoxicity, so the magnesium alloy meets the use requirements of medical materials. However, the existing technology still cannot meet the actual application requirements. The Mg-Zn-Mn-Zr system usually has poor corrosion resistance, and its mechanics still cannot meet the requirements of some high-mechanical performance implants. It is still necessary to optimize the refinement of alloy grains, the enhancement of mechanical properties and corrosion resistance.
[0004] Therefore, there is an urgent need for a highly corrosion-resistant and controllably degradable medical magnesium alloy, which can avoid aggravating the microgalvanic corrosion of the magnesium matrix by adding a small amount of low-potential alloying elements, and promote the uniform and fine dispersion of the second phase in the magnesium matrix through deformation processing and heating treatment regulation, thereby further weakening the microgalvanic corrosion and effectively avoiding the occurrence of local corrosion to promote the uniform degradation of the alloy. In addition, it can also effectively improve the mechanical properties of the magnesium alloy. Summary of the invention
[0005] The purpose of the present invention is to provide a highly corrosion-resistant and controllably degradable medical magnesium alloy and a preparation method thereof. By using a magnesium-calcium master alloy, a magnesium-yttrium master alloy, a magnesium-lanthanum master alloy and a manganese source to introduce other alloy elements, the mechanical properties and corrosion resistance of the magnesium alloy are improved through a comprehensive effect; at the same time, by means of a deformation processing and heating treatment control method, the second phase in the magnesium matrix is promoted to be uniformly and finely dispersed, and high corrosion resistance is further obtained. At the same time, local corrosion can be avoided, and uniform and controllable degradation of the alloy is achieved.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy, comprising the following steps:
[0008] Step (1): preheating the pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source to remove moisture;
[0009] Step (2): smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source into a graphite crucible in sequence and melting them to obtain a magnesium alloy melt;
[0010] Step (3): refining, stirring, and standing the magnesium alloy melt in sequence to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt;
[0011] Step (4): removing the oxidized slag on the surface of the purified magnesium alloy melt, and then casting it into a preheated metal mold to obtain a magnesium alloy ingot;
[0012] Step (5): first subjecting the magnesium alloy ingot to a solid solution treatment, and then extruding it into a rod; subjecting the rod to a rotary forging treatment on a rotary forging machine to obtain a rotary forged rod; subjecting the rotary forged rod to an aging treatment to obtain a highly corrosion-resistant and controllably degradable medical magnesium alloy;
[0013] Among them, calculated by mass percentage, the highly corrosion-resistant and controllably degradable medical magnesium alloy includes 6-6.5wt% zinc, 0.1-0.15wt% calcium, 0.1-0.15wt% yttrium, 0.1-0.15wt% lanthanum, 0.1-0.15wt% manganese and the remainder magnesium.
[0014] As a preferred solution, the volume ratio of carbon dioxide to sulfur hexafluoride in step (2) is 1:(9-10); the adding process is: adding pure magnesium ingot at 600-620°C until it is completely melted, adding manganese source and zinc powder at 700-720°C until they are completely melted, and adding magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy at 750-760°C until they are completely melted.
[0015] As a preferred solution, the refining treatment in step (3) is as follows: adding a refining agent to the magnesium alloy melt, and then stirring for 10 to 20 minutes at a temperature of 750 to 760°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the static insulation treatment is as follows: first standing at 740 to 750°C for 30 to 40 minutes, and then cooling to 700 to 710°C and standing for 20 to 30 minutes.
[0016] As a preferred solution, the casting temperature in step (4) is 690-700°C, and the metal mold preheating temperature is 180-200°C.
[0017] As a preferred solution, the solution treatment temperature in step (5) is 330-350°C, and the time is 24-30h; the extrusion process temperature is 330-350°C, and the extrusion speed is 0.5-1m / min; the aging treatment temperature is 175-200°C, and the aging time is 12-24h.
[0018] As a preferred solution, the preparation method of the magnesium-calcium master alloy comprises: weighing 90-100 parts of magnesium oxide, 5-10 parts of calcium oxide and 50-60 parts of aluminum powder by weight, mixing them evenly, pressing them into agglomerates under a pressure of 60-70 MPa, and then keeping them warm for 4-5 hours under a vacuum degree of 1-10 Pa and a temperature of 1200-1250° C. to reduce the magnesium oxide and calcium oxide to magnesium vapor and calcium vapor; and obtaining the magnesium-calcium master alloy in a crystallizer after condensing the magnesium vapor and calcium vapor.
[0019] The crystal structure of magnesium-calcium master alloy is optimized by adding calcium. As an alkali metal element, calcium has the function of refining grains. A small amount of calcium added to the magnesium alloy melt can form heterogeneous nucleation particles, promote a large number of heterogeneous nucleation of magnesium crystals in the melt and refine the grains, and significantly improve the mechanical properties of the alloy through grain refinement strengthening.
[0020] As a preferred solution, the preparation method of the magnesium-yttrium master alloy comprises: weighing 80-90 parts of magnesium particles and 10-20 parts of yttrium powder by weight, mixing them evenly to obtain a mixed powder, and pressing the mixed powder into a round block using a tablet press; placing the round block in an argon atmosphere, under a vacuum degree of 1-5 Pa, heating from room temperature to 780-800°C at a rate of 2°C / min, keeping the temperature for 2-3 hours, and then cooling to 20-30°C to obtain a magnesium-yttrium master alloy.
[0021] Yttrium can be used as an excellent additive component to refine the alloy's dendrite structure and improve the alloy's plasticity. In addition, it can better improve the creep resistance of magnesium alloys, thereby improving the mechanical properties of the alloy material. At the same time, yttrium can form a stable oxide film to improve the corrosion resistance of magnesium alloys.
[0022] As a preferred solution, the preparation method of the magnesium-lanthanum intermediate alloy comprises: weighing 85-95 parts of magnesium chloride and 5-10 parts of anhydrous lanthanum chloride in parts by weight, adding them to 300-400 parts of benzene, and then adding 50-80 parts of tetrahydrofuran and stirring for 6-8 hours to obtain a mixed solution; using a platinum sheet as an anode, a copper sheet as a cathode, and the mixed solution as a plating solution, controlling the current density to 50-60 mA / cm², and performing electrodeposition for 1-2 hours. After the electrodeposition is completed, the deposit is peeled off from the electrode to obtain a magnesium-lanthanum intermediate alloy.
[0023] Impurities in alloy materials usually destroy the continuity and microstructure of the magnesium matrix by forming defects such as pores and cracks near the grain boundaries; the preparation of magnesium-lanthanum master alloys by electrodeposition technology can effectively reduce the impurity components of magnesium-lanthanum master alloys. Traditionally smelted magnesium-lanthanum master alloys usually contain a high content of impurities, such as Fe, which will significantly deteriorate the corrosion resistance of magnesium alloys. This method can reduce the corrosion that may be caused by impurities, thereby improving the corrosion resistance of magnesium alloys.
[0024] As a preferred solution, the manganese source is a magnesium-manganese master alloy and / or anhydrous manganese chloride; the magnesium-manganese master alloy can be prepared by referring to the method described in "CN107746981A".
[0025] The second aspect of the present invention provides a highly corrosion-resistant and controllably degradable medical magnesium alloy prepared by the preparation method described in the first aspect.
[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0027] 1. The present invention adopts magnesium-zinc alloy with good biocompatibility as the basis, and performs microalloying treatment by adding a small amount of low-potential calcium, yttrium and lanthanum elements. First, magnesium-zinc alloy has excellent ductility, which is conducive to subsequent deformation treatment. On the other hand, the addition of zinc can play a role in solid solution strengthening and improve the mechanical properties of the alloy. On the one hand, calcium has good biocompatibility, which can promote the proliferation and differentiation of bone cells and induce bone regeneration. On the other hand, it has a lower standard electrode potential than magnesium, which can reduce the increase in the potential of the magnesium matrix caused by the addition of zinc, so that the potential difference between the magnesium matrix and the second phase is reduced. Yttrium and lanthanum elements also have standard electrode potentials similar to magnesium, and the addition of a small amount of alloying elements will not aggravate the microgalvanic corrosion of the magnesium matrix; in addition, lanthanum has the effect of inhibiting tumor proliferation, and yttrium has no obvious toxicity to the human body. The addition of a small amount of manganese has good biocompatibility, which can promote bone induction and bone regeneration. In addition, the addition of manganese has the effect of removing impurity iron elements in the melt, thereby reducing the influence of impurity iron elements on corrosion resistance.
[0028] 2. The present invention adopts a preparation method of traditional casting plus extrusion primary deformation plus rotary forging secondary deformation, which further improves the corrosion resistance and mechanical properties of the alloy by significantly refining the grains and breaking up the coarse network second phase; through subsequent aging treatment, a uniform, fine and dispersed second phase structure can be formed in the matrix, which is beneficial to promote the uniform degradation of the alloy and avoid the occurrence of local corrosion.
[0029] 3. The present invention is based on low-cost magnesium-zinc-based alloys and adds a small amount of low-cost calcium, yttrium, lanthanum, and manganese elements, which has the advantage of low cost. In addition, by adopting the preparation method of traditional gravity casting plus conventional extrusion and rotary forging, large-sized bars can be prepared on a large scale, and further machining can be prepared into magnesium alloy implants of various structures, such as bone nails and bone plates. Compared with the selective laser melting metal 3D printing technology using magnesium alloy powder, the preparation method of the present invention is safer and easier to implement.
[0030] 4. The present invention introduces other alloy elements by using magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy, wherein the magnesium-calcium master alloy is optimized in crystal structure by adding calcium element, and calcium element as an alkali metal element has the effect of refining grains, producing fine grain strengthening effect and thus improving mechanical properties; yttrium element can refine the dendrite structure of the alloy, improve the mechanical properties of the alloy material, and form a stable oxide film at the same time, thereby increasing the corrosion resistance of the magnesium alloy; the magnesium-lanthanum master alloy is prepared by electrodeposition technology, which can effectively reduce the impurity components of the magnesium-lanthanum master alloy, thereby improving the corrosion resistance of the magnesium alloy; the comprehensive effect of multiple elements improves the mechanical properties and corrosion resistance of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the SEM image of the microstructure of the magnesium alloy prepared in Example 1.
[0032] Figure 2 This is a SEM image of the cross-sectional corrosion morphology of the magnesium alloy in Example 1 immersed in a 37° C. SBF solution for 7 days;
[0033] Figure 3 This is the SEM image of the cross-sectional corrosion morphology of commercial pure magnesium in Comparative Example 7 immersed in a 37°C SBF solution for 7 days. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The sources of some components in the embodiments and comparative examples are as follows:
[0036] Pure magnesium ingot, purity ≥99.9, purchased from Shenzhen Datang Metal Materials Co., Ltd.;
[0037] Magnesium particles, CAS No. 7439-95-4, were purchased from Hebei Qinbang New Materials Technology Co., Ltd.;
[0038] Zinc powder, product number FZAP-300F, was purchased from Hebei Ruojia Technology New Material Technology Co., Ltd.;
[0039] Magnesium-manganese master alloy, prepared by referring to the method described in Chinese patent "CN107746981A";
[0040] Anhydrous manganese chloride, CAS No. 7773-01-5, was purchased from Shanghai McLean Biochemical Technology Co., Ltd., China;
[0041] Potassium chloride, CAS No. 7447-40-7, purchased from Xilong Chemical Co., Ltd.;
[0042] Calcium chloride, CAS No. 10043-52-4, was purchased from Shanghai McLean Biochemical Technology Co., Ltd., China;
[0043] Barium chloride, CAS No. 10361-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0044] Calcium fluoride, CAS No. 7789-75-5, purchased from Shanghai Aladdin Co., Ltd.;
[0045] Yttrium chloride, CAS No. 10361-92-9, purchased from Shanghai Aladdin Co., Ltd.;
[0046] Magnesium oxide, CAS No. 1309-48-4, was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.;
[0047] Calcium oxide, CAS No. 1305-78-8, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0048] Aluminum powder, spherical, D50: 9~11μm, purity ≥99.8%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0049] Yttrium powder, CAS No. 7440-65-5, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0050] Magnesium chloride, CAS No. 14989-29-8, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0051] Anhydrous lanthanum chloride, CAS No. 10099-58-8, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0052] Benzene, CAS No. 71-43-2, purchased from Shanghai Anaiji Chemical Co., Ltd.;
[0053] Tetrahydrofuran, CAS No. 109-99-9, purchased from Shanghai Anaiji Chemical Co., Ltd.;
[0054] Platinum sheet, model 20*20*0.1 mm, purchased from Shanghai Yueci Electronic Technology Co., Ltd.;
[0055] Copper sheet, item number ZTD2018090T2, purchased from Dongguan Xinye Metal Materials Co., Ltd.;
[0056] Pure magnesium block, CAS No. 7439-95-4, was purchased from Shandong Ruifeng Metal Products Co., Ltd.
[0057] Example 1
[0058] This embodiment provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy, comprising the following steps:
[0059] Preparation of magnesium-calcium master alloy: 100 parts of magnesium oxide, 10 parts of calcium oxide and 60 parts of aluminum powder are weighed in parts by weight, mixed evenly and pressed into agglomerates under a pressure of 70 MPa, and then kept warm for 4 hours at a vacuum degree of 10 Pa and a temperature of 1250°C to reduce the magnesium oxide and calcium oxide to magnesium vapor and calcium vapor; after the magnesium vapor and calcium vapor are condensed, a magnesium-calcium master alloy is obtained in a crystallizer.
[0060] Preparation of magnesium-yttrium intermediate alloy: 90 parts of magnesium particles and 20 parts of yttrium powder are weighed by weight and mixed evenly to obtain a mixed powder, and the mixed powder is pressed into a round block using a tablet press; the round block is placed in an argon atmosphere, and under a vacuum degree of 5 Pa, the temperature is increased from room temperature to 800°C at a rate of 2°C / min, kept warm for 2 hours, and then cooled to 30°C to obtain a magnesium-yttrium intermediate alloy.
[0061] Preparation of magnesium-lanthanum master alloy: 95 parts of magnesium chloride and 10 parts of anhydrous lanthanum chloride are weighed in parts by weight and added to 400 parts of benzene, and then 80 parts of tetrahydrofuran are added and stirred for 8 hours to obtain a mixed solution; a platinum sheet is used as an anode, a copper sheet is used as a cathode, and the mixed solution is used as a plating solution. The current density is controlled to be 60mA / cm², and the electrodeposition is carried out for 1 hour. After the electrodeposition is completed, the deposit is peeled off from the electrode to obtain a magnesium-lanthanum master alloy.
[0062] Step (1): preheating the pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source to remove moisture; the manganese source is anhydrous manganese chloride;
[0063] Step (2): smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and anhydrous manganese chloride into a graphite crucible in sequence and melting them to obtain a magnesium alloy melt; the volume ratio of carbon dioxide to sulfur hexafluoride is 1:9; the adding process is adding pure magnesium ingot at 600° C. until it is completely melted, adding anhydrous manganese chloride and zinc powder at 700° C. until they are completely melted, and adding magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy at 760° C. until they are completely melted;
[0064] Step (3): refining, stirring, and standing and heat-insulating the magnesium alloy melt in sequence to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining treatment comprises adding a refining agent to the magnesium alloy melt, and then stirring for 10 minutes at a temperature of 750°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent comprises 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat-insulating treatment comprises first standing at 750°C for 30 minutes, then cooling to 710°C and standing for 20 minutes;
[0065] Step (4): removing the oxidized slag on the surface of the purified magnesium alloy melt, and then casting it into a preheated metal mold to obtain a magnesium alloy ingot; the casting temperature is 690° C., and the preheating temperature of the metal mold is 180° C.;
[0066] Step (5): first subjecting the magnesium alloy ingot to a solid solution treatment, and then extruding it into a rod; subjecting the rod to a rotary forging treatment on a rotary forging machine to obtain a rotary forging rod; subjecting the rotary forging rod to an aging treatment to obtain a highly corrosion-resistant and controllably degradable medical magnesium alloy; the solid solution treatment temperature is 350°C and the time is 24h; the extrusion process temperature is 350°C and the extrusion speed is 1m / min; the aging treatment temperature is 175°C and the aging time is 12h;
[0067] Wherein, calculated by mass percentage, the highly corrosion-resistant and controllably degradable medical magnesium alloy includes 6.04wt% zinc, 0.12wt% calcium, 0.11wt% yttrium, 0.1wt% lanthanum, 0.12wt% manganese and the remainder magnesium.
[0068] Figure 1 The SEM image of the microstructure of this embodiment shows that the alloy has a fine dispersed second phase structure.
[0069] Example 2
[0070] This embodiment provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy, comprising the following steps:
[0071] Preparation of magnesium-calcium master alloy: 90 parts of magnesium oxide, 5 parts of calcium oxide and 50 parts of aluminum powder are weighed in parts by weight, mixed evenly and pressed into agglomerates under a pressure of 60 MPa, and then kept warm for 5 hours at a vacuum degree of 1 Pa and a temperature of 1200°C to reduce the magnesium oxide and calcium oxide to magnesium vapor and calcium vapor; after the magnesium vapor and calcium vapor are condensed, a magnesium-calcium master alloy is obtained in a crystallizer.
[0072] Preparation of magnesium-yttrium intermediate alloy: 80 parts of magnesium particles and 10 parts of yttrium powder are weighed by weight and mixed evenly to obtain a mixed powder, and the mixed powder is pressed into a round block using a tablet press; the round block is placed in an argon atmosphere, and under a vacuum degree of 1 Pa, the temperature is increased from room temperature to 780°C at a rate of 2°C / min, and the temperature is kept for 3 hours, and then cooled to 20°C to obtain a magnesium-yttrium intermediate alloy.
[0073] Preparation of magnesium-lanthanum master alloy: 85 parts of magnesium chloride and 5 parts of anhydrous lanthanum chloride are weighed in parts by weight and added to 300 parts of benzene, and then 50 parts of tetrahydrofuran are added and stirred for 6 hours to obtain a mixed solution; a platinum sheet is used as an anode, a copper sheet is used as a cathode, and the mixed solution is used as a plating solution. The current density is controlled to be 50mA / cm², and the electrodeposition is carried out for 2 hours. After the electrodeposition is completed, the deposit is peeled off from the electrode to obtain a magnesium-lanthanum master alloy.
[0074] Step (1): preheating the pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source to remove moisture; the manganese source is magnesium-manganese master alloy;
[0075] Step (2): smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and magnesium-manganese master alloy into a graphite crucible in turn and melting them to obtain a magnesium alloy melt; the volume ratio of carbon dioxide to sulfur hexafluoride is 1:10; the adding process is adding pure magnesium ingot at 620°C until it is completely melted, adding magnesium-manganese master alloy and zinc powder at 720°C until they are completely melted, and adding magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy at 750°C until they are completely melted;
[0076] Step (3): refining, stirring, and standing and heat-insulating the magnesium alloy melt in sequence to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining treatment comprises adding a refining agent to the magnesium alloy melt, and then stirring the melt at a temperature of 760° C. for 20 minutes; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent comprises, by weight, 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride, and 3 parts of yttrium chloride; the standing and heat-insulating treatment comprises first standing at 740° C. for 40 minutes, then cooling to 700° C. and standing for 30 minutes;
[0077] Step (4): removing the oxide slag on the surface of the purified magnesium alloy melt, and then casting it into a preheated metal mold to obtain a magnesium alloy ingot; the casting temperature is 700° C., and the preheating temperature of the metal mold is 200° C.;
[0078] Step (5): first subjecting the magnesium alloy ingot to a solid solution treatment, and then extruding it into a rod; subjecting the rod to a rotary forging treatment on a rotary forging machine to obtain a rotary forging rod; subjecting the rotary forging rod to an aging treatment to obtain a highly corrosion-resistant and controllably degradable medical magnesium alloy; the solid solution treatment temperature is 330°C and the time is 30h; the extrusion process temperature is 330°C and the extrusion speed is 0.5m / min; the aging treatment temperature is 200°C and the aging time is 24h;
[0079] Wherein, calculated by mass percentage, the highly corrosion-resistant and controllably degradable medical magnesium alloy includes 6wt% zinc, 0.1wt% calcium, 0.1wt% yttrium, 0.1wt% lanthanum, 0.1wt% manganese and the remainder magnesium.
[0080] The microstructure of this embodiment is similar to that of embodiment 1.
[0081] Example 3
[0082] This embodiment provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy, comprising the following steps:
[0083] Preparation of magnesium-calcium master alloy: 95 parts of magnesium oxide, 8 parts of calcium oxide and 58 parts of aluminum powder are weighed in parts by weight, mixed evenly and pressed into agglomerates under a pressure of 65 MPa, and then kept warm for 5 hours at a vacuum degree of 6 Pa and a temperature of 1230°C to reduce the magnesium oxide and calcium oxide to magnesium vapor and calcium vapor; after the magnesium vapor and calcium vapor are condensed, a magnesium-calcium master alloy is obtained in a crystallizer.
[0084] Preparation of magnesium-yttrium intermediate alloy: 85 parts of magnesium particles and 18 parts of yttrium powder are weighed and mixed evenly to obtain a mixed powder, and the mixed powder is pressed into a round block using a tablet press; the round block is placed in an argon atmosphere, and under a vacuum degree of 3 Pa, the temperature is increased from room temperature to 790°C at a rate of 2°C / min, kept warm for 2 hours, and then cooled to 25°C to obtain a magnesium-yttrium intermediate alloy.
[0085] Preparation of magnesium-lanthanum master alloy: 88 parts of magnesium chloride and 9 parts of anhydrous lanthanum chloride are weighed in parts by weight and added to 360 parts of benzene, and then 60 parts of tetrahydrofuran are added and stirred for 7 hours to obtain a mixed solution; a platinum sheet is used as an anode, a copper sheet is used as a cathode, and the mixed solution is used as a plating solution. The current density is controlled to be 55mA / cm², and the electrodeposition is carried out for 2 hours. After the electrodeposition is completed, the deposit is peeled off from the electrode to obtain a magnesium-lanthanum master alloy.
[0086] Step (1): preheating the pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source to remove moisture; the manganese source is anhydrous manganese chloride;
[0087] Step (2): smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and anhydrous manganese chloride into a graphite crucible in sequence and melting them to obtain a magnesium alloy melt; the volume ratio of carbon dioxide to sulfur hexafluoride is 1:10; the adding process is adding pure magnesium ingot at 610°C until it is completely melted, adding anhydrous manganese chloride and zinc powder at 710°C until they are completely melted, and adding magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy at 755°C until they are completely melted;
[0088] Step (3): refining, stirring, and standing and heat-insulating the magnesium alloy melt in sequence to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining treatment comprises adding a refining agent to the magnesium alloy melt, and then stirring for 15 minutes at a temperature of 755°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent comprises 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat-insulating treatment comprises first standing at 748°C for 35 minutes, then cooling to 705°C and standing for 28 minutes;
[0089] Step (4): removing the oxidized slag on the surface of the purified magnesium alloy melt, and then casting it into a preheated metal mold to obtain a magnesium alloy ingot; the casting temperature is 696° C., and the preheating temperature of the metal mold is 190° C.;
[0090] Step (5): first subjecting the magnesium alloy ingot to a solid solution treatment, and then extruding it into a rod; subjecting the rod to a rotary forging treatment on a rotary forging machine to obtain a rotary forging rod; subjecting the rotary forging rod to an aging treatment to obtain a highly corrosion-resistant and controllably degradable medical magnesium alloy; the solid solution treatment temperature is 340°C and the time is 28h; the extrusion process temperature is 340°C and the extrusion speed is 0.8m / min; the aging treatment temperature is 190°C and the aging time is 20h;
[0091] Wherein, calculated by mass percentage, the highly corrosion-resistant and controllably degradable medical magnesium alloy includes 6.5wt% zinc, 0.15wt% calcium, 0.15wt% yttrium, 0.15wt% lanthanum, 0.15wt% manganese and the remainder magnesium.
[0092] The microstructure of this embodiment is similar to that of embodiment 1.
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that no magnesium-yttrium master alloy, magnesium-lanthanum master alloy and anhydrous manganese chloride are added, and the rest is the same as Example 1.
[0095] Comparative Example 2
[0096] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that no magnesium-calcium master alloy, magnesium-lanthanum master alloy and anhydrous manganese chloride are added, and the rest is the same as Example 1.
[0097] Comparative Example 3
[0098] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that no magnesium-calcium master alloy, magnesium-yttrium master alloy and anhydrous manganese chloride are added, and the rest is the same as Example 1.
[0099] Comparative Example 4
[0100] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that no magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy are added, and the rest is the same as Example 1.
[0101] Comparative Example 5
[0102] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that no magnesium-lanthanum intermediate alloy and anhydrous manganese chloride are added, and the rest is the same as Example 1.
[0103] Comparative Example 6
[0104] This comparative example provides a method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy. The difference between this comparative example and Example 1 is that anhydrous manganese chloride is not added, and the rest is the same as Example 1.
[0105] Comparative Example 7
[0106] Comparative Example 7 is a commercially available pure magnesium block, which is used for performance comparison.
[0107] Performance Testing
[0108] The magnesium alloys prepared in the above examples and comparative examples and the pure magnesium block of comparative example 7 were subjected to the following tests:
[0109] (1) Mechanical properties test
[0110] The mechanical properties test complies with the requirements of "GB / T 228.1-2021 Tensile test of metallic materials Part 1: Room temperature test method". The gauge size of the tensile test piece is 20×4×2 mm, and three parallel test specimens are used.
[0111] (2) Corrosion performance test
[0112] The corrosion test solution is simulated body fluid (SBF, purchased from Solebold), the test temperature is 37°C in a water bath, the size of the test sample is 20×20×5mm, and the test time is 7 days. The immersion corrosion test complies with the requirements of the national standard "GB 10124-88 Metal Materials Laboratory Uniform Corrosion Full Immersion Test Method", and the corrosion cleaning agent complies with the requirements of the national standard "GB∕T 16545-2015 Removal of Corrosion Products on Corrosion Test Specimens of Metals and Alloys". The weight loss rate is calculated by calculating the difference between the weight of the sample before the corrosion test and the weight of the sample after the corrosion test cleaning. Weight loss rate (mg / cm 2 / day) is equal to the weight difference divided by the surface area of the sample divided by the number of test days; it can be converted into the average depth corrosion rate (mm / year) by conversion; the reduction of the solution in the burette is recorded by the hydrogen evolution test device to be equivalent to the volume of hydrogen gas released by magnesium corrosion, and the hydrogen evolution rate (mL / cm) is obtained by dividing the volume of hydrogen gas released by the surface area of the sample divided by the number of test days. 2 / day).
[0113] The performance test results are shown in Table 1:
[0114] Table 1 Performance test results
[0115]
[0116] From the above performance test results, it can be seen that Examples 1-3 have good effects, with yield strength of 336-353 MPa, tensile strength of 375-387 MPa, and weight loss rate of 0.15-0.18 mg / cm 2 / day, hydrogen evolution rate 0.16~0.32mL / cm 2 / day, the corrosion rate is 0.32~0.38mm / y; this is because it introduces other alloying elements by using magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source, thereby comprehensively improving the mechanical properties and corrosion resistance of magnesium alloy.
[0117] Figure 2 This is the corrosion cross-sectional morphology of Example 1 immersed in SBF solution at 37° C. for 7 days. It can be seen that the corrosion products are uniform in thickness and dense, achieving uniform and controllable degradation of the alloy under a physiological environment.
[0118] The comparative example did not adopt the necessary technical solution, resulting in that the corresponding performance tests were significantly worse than those of the embodiment. Compared with Example 1, the comparative example 1 did not add the magnesium-yttrium master alloy, the magnesium-lanthanum master alloy and the anhydrous manganese chloride, so the yield strength and tensile strength decreased, and the weight loss rate, hydrogen evolution rate and corrosion rate increased; compared with Example 1, the comparative example 2 did not add the magnesium-calcium master alloy, the magnesium-lanthanum master alloy and the anhydrous manganese chloride, so the yield strength and tensile strength decreased, and the weight loss rate, hydrogen evolution rate and corrosion rate increased; compared with Example 1, the comparative example 2 did not add the magnesium-calcium master alloy, the magnesium-lanthanum master alloy and the anhydrous manganese chloride, so the yield strength and tensile strength decreased, and the weight loss rate, hydrogen evolution rate and corrosion rate increased; compared with Example 2 Compared with Example 1, Comparative Example 3 did not add magnesium-calcium master alloy, magnesium-yttrium master alloy and anhydrous manganese chloride, so the yield strength and tensile strength decreased, and the weight loss rate, hydrogen evolution rate and corrosion rate increased; Compared with Example 1, Comparative Example 4 did not add magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy, so the yield strength and tensile strength decreased, and the weight loss rate, hydrogen evolution rate and corrosion rate increased; Compared with Example 1, Comparative Example 5 did not add magnesium-lanthanum master alloy and anhydrous manganese chloride, so the weight loss rate, hydrogen evolution rate and corrosion rate increased. Compared with Example 1, Comparative Example 6 did not add anhydrous manganese chloride, so the weight loss rate, hydrogen evolution rate and corrosion rate increased; Comparative Example 7 is a commercial pure magnesium block, the mechanical properties cannot be measured, and the corrosion performance is the worst. Figure 3 The SEM image of the corrosion cross section of commercial pure magnesium after being immersed in 37°C SBF solution for 7 days. It can be seen that traditional pure magnesium has a serious tendency to local corrosion in a physiological environment, and the corrosion rate is uncontrollable. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0119] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy, characterized in that: The following steps are involved: Step (1): preheating the pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source to remove moisture; Step (2): smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding pure magnesium ingot, zinc powder, magnesium-calcium master alloy, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and manganese source into a graphite crucible in sequence and melting them to obtain a magnesium alloy melt; Step (3): refining, stirring, and standing the magnesium alloy melt in sequence to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; Step (4): removing the oxidized slag on the surface of the purified magnesium alloy melt, and then casting it into a preheated metal mold to obtain a magnesium alloy ingot; Step (5): first subjecting the magnesium alloy ingot to a solid solution treatment, and then extruding it into a rod; subjecting the rod to a rotary forging treatment on a rotary forging machine to obtain a rotary forged rod; subjecting the rotary forged rod to an aging treatment to obtain a highly corrosion-resistant and controllably degradable medical magnesium alloy; Among them, calculated by mass percentage, the highly corrosion-resistant and controllably degradable medical magnesium alloy includes 6-6.5wt% zinc, 0.1-0.15wt% calcium, 0.1-0.15wt% yttrium, 0.1-0.15wt% lanthanum, 0.1-0.15wt% manganese and the remainder magnesium.
2. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The volume ratio of carbon dioxide to sulfur hexafluoride in step (2) is 1:(9-10); the adding process is: adding pure magnesium ingot at 600-620° C. until it is completely melted, adding manganese source and zinc powder at 700-720° C. until they are completely melted, and adding magnesium-calcium master alloy, magnesium-yttrium master alloy and magnesium-lanthanum master alloy at 750-760° C. until they are completely melted.
3. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The refining treatment in step (3) is as follows: A refining agent is added to the melt, and then stirred for 10 to 20 minutes at a temperature of 750 to 760°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the static insulation treatment is: first standing at 740 to 750°C for 30 to 40 minutes, and then cooling to 700 to 710°C and standing for 20 to 30 minutes.
4. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The casting temperature in step (4) is 690-700°C, and the metal mold preheating temperature is 180-200°C.
5. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The solution treatment temperature in step (5) is 330-350°C, and the time is 24-30h; the extrusion process temperature is 330-350°C, and the extrusion speed is 0.5-1m / min; the aging treatment temperature is 175-200°C, and the aging time is 12-24h.
6. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The preparation method of the magnesium-calcium master alloy comprises: weighing 90-100 parts of magnesium oxide, 5-10 parts of calcium oxide and 50-60 parts of aluminum powder by weight, mixing them evenly, pressing them into agglomerates under a pressure of 60-70 MPa, and then keeping them warm for 4-5 hours under a vacuum degree of 1-10 Pa and a temperature of 1200-1250° C. to reduce the magnesium oxide and calcium oxide into magnesium vapor and calcium vapor; and obtaining the magnesium-calcium master alloy in a crystallizer after condensing the magnesium vapor and the calcium vapor.
7. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The preparation method of the magnesium-yttrium master alloy comprises: weighing 80-90 parts of magnesium particles and 10-20 parts of yttrium powder by weight, mixing them evenly to obtain a mixed powder, and pressing the mixed powder into a round block by using a tablet press; placing the round block in an argon atmosphere, heating the temperature from room temperature to 780-800° C. at a heating rate of 2° C. / min under a vacuum degree of 1-5 Pa, keeping the temperature for 2-3 hours, and then cooling the temperature to 20-30° C. to obtain the magnesium-yttrium master alloy.
8. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The preparation method of the magnesium-lanthanum intermediate alloy comprises: weighing 85-95 parts of magnesium chloride and 5-10 parts of anhydrous lanthanum chloride in parts by weight, adding them into 300-400 parts of benzene, and then adding 50-80 parts of tetrahydrofuran and stirring for 6-8 hours to obtain a mixed solution; using a platinum sheet as an anode, a copper sheet as a cathode, and the mixed solution as a plating solution, controlling the current density to 50-60 mA / cm², performing electrodeposition for 1-2 hours, and after the electrodeposition is completed, peeling off the sediment and the electrode to obtain the magnesium-lanthanum intermediate alloy.
9. The method for preparing a highly corrosion-resistant and controllably degradable medical magnesium alloy according to claim 1, characterized in that: The manganese source is a magnesium-manganese master alloy and / or anhydrous manganese chloride.
10. A highly corrosion-resistant and controllably degradable medical magnesium alloy, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing magnesium-manganese intermediate alloy
CN107746981A
Preparation method of degradable medical magnesium alloy
CN116694943A
Rare earth magnesium alloy and preparation method thereof
CN102899545A
High-strength high-toughness high-modulus deformed magnesium alloy and preparation method thereof
CN109972009A